Subclinical anthracycline-induced cardiotoxicity in long-term follow-up of asymptomatic childhood cancer survivors: Assessment by speckle tracking echocardiography - (:unkn) unknown (WILEY, 2018)
ObjectiveSurvivors of childhood cancer treated with anthracyclines carry the risk for developing late-onset cardiotoxicity. The purpose of this study was to evaluate left ventricular (LV) function in this patient group and compare it with healthy controls by means of conventional and speckle tracking echocardiography (STE) after exposure to chemotherapy. Material and methodsConventional and STE were performed in 45 childhood cancer survivors (mean age 114.6; 26 male) treated with anthracyclines (median cumulative dosage 240mg/m(2); range, 100-460) and compared with age, gender and body surface area matched healthy controls. Follow-up period after chemotherapy was 21.917.8months. Blood samples were taken from survivors and controls to determine brain natriuretic peptide (BNP). ResultsFollowing anthracycline exposure, pediatric cancer survivors had lower longitudinal, radial anteroseptal, and radial anterior strain values compared to controls (P<.05). The calculated global longitudinal and global radial strain values were lower compared to the control group (P<.05). Both groups had normal ejection fraction (EF) and fractional shortening (FS). Brain natriuretic peptide (BNP) levels of both groups were in the normal range. ConclusionDespite normal EF and FS, children exposed to anthracycline therapy may have late-onset subtle changes of LV strain values measured by STE. Whether these changes of strain can predict future risk of developing heart failure needs to be explored in further studies.
Keywords: cardiac toxicity; left ventricular function; strain; transthoracic echocardiography; 2-DIMENSIONAL STRAIN; LONGITUDINAL STRAIN; CHILDREN; THERAPY; TOXICITY; FAILURE; ADULTS